0263 Can workplace chest X-ray surveillance programs shed light on workers' injuries? Prevalence and predictors of rib fractures among active and former Ukrainian coal miners. (23rd June 2014) - Graber, Judith M; Cohen, Robert A; Basanets, Angela; Kundiev, Yuri; Mukhin, Vladimir; Lysenko, Olga; Zvinchuk, Alexander; Hryhorczuk, Daniel
Abstract : Objectives: Chest x-ray surveillance programs for pneumoconiosis are well established public health tools. Data on rib fractures, part of the ILO system of classification, may shed light on injuries in these populations. We sought to determine the prevalence of rib fractures from a cross-sectional study of current and former Ukrainian coal miners. Method: Between 2001 and 2003, coal miners with at least five years of underground mining experience were randomly selected from employment records of 7000 current and 9000 former miners from three mines. CXRs were read by two NIOSH B-readers. Interviewers collected work and smoking history. The prevalence and predictors of at least one rib fracture with 95% confidence intervals [95% CIs] was estimated using univariate methods and logistic regression. Results: Average age was 47.1 years among the 598 active miners and 56.9 years among the 468 former miners. Total mining tenure and years of work at the coal face were similar in both groups, about 20 and 8 years respectively. The prevalence of rib fractures was almost twice as high in former compared with current miners (15.5% [11.6, 19.5%] vs. 7.9% [5.6, 13.3%], respectively). Prevalence increased with age among active miners; among former miners prevalence was highest in 45 to 55 year olds. Conclusions: CXR surveillance for pneumoconiosis may have use in monitoring injury among miners. While the prevalence of rib fracture appeared high in this population, caution is warranted interpreting our findings: no comparison groups exist and the use of this methodology for characterising injury prevalence is untested.